How to train supply managers – Necessary and sufficient purchasing skills leading to success. Issue 4 (October 2021) - Stek, Klaas; Schiele, Holger
Abstract: The success of purchasing and supply management (PSM) largely depends on PSM professionals' skills levels. Past research assumed that one universal PSM professional type exists, and they have proposed one-size-fits-all PSM skillsets. However, PSM professionals have different objectives. Based on the data of an extensive survey conducted amongst European PSM professionals (n = 366), this study presents skillsets for seven objectives (reducing costs and improving delivery, quality, sustainability, strategic competitive advantage, supplier satisfaction and innovation). A differentiation is made between "necessary" and "sufficient" conditions for each objective's effectiveness. Within a new PSM-skills taxonomy, a hierarchy of skills is detected as one of the first categories that provide quantitative evidence that soft skills or personal skills are necessary conditions for carrying out hard skills or professional skills. Based on the proposed skillsets, university educators and firm trainers can draft teaching plans that support the intended outcome, while individual PSM professionals may get an orientation on how to develop their skills further. Highlights: 15 Empirically validated purchasing skills factors. Skillsets according to purchasing objectives. Distiction between necessary and sufficient conditions.